Association of testosterone levels and steroid 5-alpha-reductase 2 polymorphisms with opioid craving - Janke, Eva; Groh, Adrian; Mühle, Christiane; Dürsteler-MacFarland, Kenneth M.; Wiesbeck, Gerhard A.; Kornhuber, Johannes; Jahn, Kirsten; Groeschl, Michael; Lichtinghagen, Ralf; Frieling, Helge; Bleich, Stefan; Hillemacher, Thomas; et al. (Neuropsychobiology, 2021)
Background/Aims: Opioid dependence is a severe disease which is associated with a high risk of relapse, even in cases of successful withdrawal therapy. Studies have shown alterations of the hypothalamic-pituitary-gonadal axis in opioid-dependent patients, such as decreased testosterone serum levels in affected males. Sex hormones and the steroid 5-alpha-reductase 2 (SRD5A2) V89L polymorphism are associated with craving during alcohol withdrawal, but little is known about their impact on symptomatology of opioid dependence. Methods: In this study, we analyzed 2 independent male cohorts of opioid-dependent patients for possible alterations in testosterone serum levels compared to non-opioid-dependent controls. In one of the cohorts, we additionally investigated associations of testosterone serum levels and 3 SRD5A2 polymorphisms with symptoms of opioid dependence, measured by the Heroin Craving Questionnaire (HCQ). Results: In the patient groups, we found significantly decreased testosterone serum levels compared to the control groups. Furthermore, we found significant associations of both the testosterone serum levels and the SRD5A2 V89L polymorphism with opioid craving assessed by the HCQ. Conclusion: Our data show a possible role of testosterone metabolism in opioid dependence, which may be relevant for the establishment of future treatment strategies.